Functions of silicon in plant drought stress responses - Wang, Min; Wang, Ruirui; Mur, Luis Alejandro Jose; Ruan, Jianyun; Shen, Qirong; Guo, Shiwei (Horticulture research, 2021)
Silicon (Si), the second most abundant element in Earth’s crust, exerts beneficial effects on the growth and productivity of a variety of plant species under various environmental conditions. However, the benefits of Si and its importance to plants are controversial due to differences among the species, genotypes, and the environmental conditions. Although Si has been widely reported to alleviate plant drought stress in both the Si-accumulating and nonaccumulating plants, the underlying mechanisms through which Si improves plant water status and maintains water balance remain unclear. The aim of this review is to summarize the morphoanatomical, physiological, biochemical, and molecular processes that are involved in plant water status that are regulated by Si in response to drought stress, especially the integrated modulation of Si-triggered drought stress responses in Si accumulators and intermediate- and excluder-type plants. The key mechanisms influencing the ability of Si to mitigate the effects of drought stress include enhancing water uptake and transport, regulating stomatal behavior and transpirational water loss, accumulating solutes and osmoregulatory substances, and inducing plant defense- associated with signaling events, consequently maintaining whole-plant water balance. This study evaluates the ability of Si to maintain water balance under drought stress conditions and suggests future research that is needed to implement the use of Si in agriculture. Considering the complex relationships between Si and different plant species, genotypes, and the environment, detailed studies are needed to understand the interactions between Si and plant responses under stress conditions.